Case Report: Reinterpretation and Reclassification of ARSB:p.Arg159Cys Variant Identified in an Emirati Patient With Hearing Loss Caused by a Pathogenic Variant in the CDH23 Gene - Al Dhahouri, Nahid; Ali, Amanat; Hertecant, Jozef; Al-Jasmi, Fatma (Frontiers in Pediatrics, 2022)
Arylsulfatase B is an enzyme present in the lysosomes that involves in the breakdown of large sugar molecules known as glycosaminoglycans (GAGs). Mutations in the gene encoding the arylsulfataseB enzyme causes lysosomal storage disorder, mucopolysaccharidosis type VI (MPS VI) or Maroteaux-Lamy syndrome. In this study, we report a case of congenital hearing loss, and an incidental finding of a likely pathogenic mutation for MPS VI identified through whole exome sequencing (WES). Sequencing results identified a pathogenic missense variant p.Arg1746Gln in CDH23 gene. However, another missense likely pathogenic variant ARSB:p.Arg159Cys was reported as an incidental finding. The patient did not have the clinical features of MPS VI, but considering the wide clinical spectrum, progressive nature of MPS VI, and the fact that a treatment for MPS VI is available to prevent disease progression, further functional and in silico studies were performed to confirm the pathogenicity of this variant. In silico tools predicted this variant to be pathogenic. Moreover, ARSB enzyme activity was found low in dried blood spot (DBS). However, the results of urine and serum GAGs as well as ARSB enzyme levels measured from patient’s fibroblast were found normal. Based on clinical and biochemical findings, ARSB:p.Arg159Cys is likely benign and did not support the diagnosis of MPS VI. However, CDH23:p.Arg1746Gln, a pathogenic variant supports the underlying cause of hearing loss. This study highlights the importance of a robust correlation between genetic results and clinical presentation, as well as functional studies, to achieve a differential diagnosis.